Phylogenetic relationships of toads of the Rhinella granulosa group (Anura: Bufonidae): a molecular perspective with comments on hybridization and introgression. (20th March 2015) - Pereyra, Martín O.; Baldo, Diego; Blotto, Boris L.; Iglesias, Patricia P.; Thomé, Maria T.C.; Haddad, Célio F.B.; Barrio‐Amorós, César; Ibáñez, Roberto; Faivovich, Julián
Abstract: The Rhinella granulosa group consists of 13 species of toads distributed throughout open areas of South America and Panama. In this paper we perform a phylogenetic analysis considering all but one species of the group, employing five nuclear and four mitochondrial genes, for up to 7910 bp per specimen. Separate phylogenetic analyses under direct optimization (DO) of nuclear and mitochondrial sequences recovered the R. granulosa group as monophyletic and revealed topological incongruence that can be explained mainly by multiple events of hybridization and introgression, both mitochondrial and nuclear. The DO combined analysis, after the exclusion of putatively introgressed or heterozygous genomes, resulted in a phylogenetic hypothesis for the R. granulosa group in which most of the species are recovered as monophyletic, but with interspecific relationships poorly supported. The optimization of morphological (adult and larval), chromosomal, and behavioural characters resulted in 12 putative phenotypic synapomorphies for this species group and some other synapomorphies for internal clades. Our results indicate the need for additional population genetic studies on R. dorbignyi and R. fernandezae to corroborate the taxonomic status of both taxa. Finally, we discuss biological and genetic characteristics of Bufonidae, as possible explanations for the common occurrence of hybridization and introgression observed in some lineages of this family.